METHODOLOGICAL PRINCIPLES OF THE CAUSAL-SYSTEM INJURY PROCESS MODELING - Voronov, V.T.; Gavrylyuk, A.O.; Gurov, O.M.; Fomina, L.V.; Vergeles K.М.; Пашинський, Я.М.; Мазур, Г.М. (World of Medicine and Biology, 2020)
The method of causal systemic modeling of the natural relations of the traumatic process is developed on the basis of practical examinations of the archive of the Regional Bureau of Forensic Expertise (FE). Constructing the dependence of the trauma process of FE has been developed by combining traditional causal and modern systemic approaches. Causal systemic modeling of temporal pattern linkage (dependence) of the trauma process allowed: differentiate between causal and non-causal relevant factors of the full cause system; diagnose relationships: cause and effect (CER) conditionality relationships (CR), link states (LS); determine the causal roles of the relevant factors. The method of quasi-formal reproduction was developed in the plane of the text of the simulated objects of the traumatic process ensured the documentary recording of information about the relevant properties of the expert objects. Obtained objective system data on the properties of objects depending on the trauma process optimized forensic assessments of the role of objects and trauma events.